Spillovers from US Government Spending Shocks : Impact on External Positions - Popescu, Adina (Spillover Notes; Spillover Notes ;, 2017)
This note analyzes the impact of preannounced government spending shocks in the United States on the real effective exchange rate and the trade balance. Using a vector autoregression framework that allows anticipated fiscal shocks to be identified using survey information, we find that preannounced spending shocks lead to a sizable real effective dollar appreciation and a worsening of both the aggregate trade balance and bilateral trade balances in a panel of partner countries. The results are robust to controlling for country-specific variables like the macroeconomic and policy conditions in the recipient countries, are generalized across regions and might have decreased during the zero-interest-lower-bound regime.